2017
DOI: 10.4103/ijri.ijri_322_16
|View full text |Cite
|
Sign up to set email alerts
|

MRI features in dengue encephalitis: A case series in South Indian tertiary care hospital

Abstract: Dengue virus, a RNA virus of family Flaviviradae is considered non-neurotropic. Increasing studies and case reports reveal neurological manifestations of dengue virus. In our case series, we have evaluated magnetic resonance imaging (MRI) findings of 3 patients with dengue fever diagnosed by positive dengue NS1 antigen with neurological symptoms, which revealed nonspecific imaging features of dengue encephalitis in two cases and dengue meningoencephalitis in one case. Autopsy findings are also correlated in 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…On DWI, Shah et al (2018) also described a dengue double donut sign similar to our eighth case [ 10 ]. Many authors have found involvement of the thalamus, basal ganglia, brainstem, peri-ventricular white matter, and cortex on MRI in cases of dengue encephalitis, which are similar to our findings [ 11 - 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…On DWI, Shah et al (2018) also described a dengue double donut sign similar to our eighth case [ 10 ]. Many authors have found involvement of the thalamus, basal ganglia, brainstem, peri-ventricular white matter, and cortex on MRI in cases of dengue encephalitis, which are similar to our findings [ 11 - 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, severe DENV and YFV infections are generally associated with systemic disease, characterized primarily by increased vasculopathy and plasma leakage from blood vessels into tissues, as well as hepatic damage/dysfunction (World Health Organization, 2009). However, there are multiple reports describing DENV-associated neurological complications such as encephalitis and DENV infection in the human brain in autopsies, as well as detection of viral antigens in placental tissues from DENV-infected mothers (Balsitis et al, 2009; Kumar et al, 2008; Ribeiro et al, 2017; Soni et al, 2017). These findings indicate that DENV may also breach the blood-brain barrier as well as reach the placenta during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Centre of bilateral thalami showed diffusion restriction and blooming in susceptibility weighted imaging (SWI) characteristic of “double doughnut sign” due to petechial hemorrhages. [ 1 2 ] Postcontrast T1 fat sat images revealed rim enhancement in thalamus surrounding the area of diffusion restriction/susceptibility artifact. The appearance in postcontrast images is an inverse of diffusion weighted imaging.…”
mentioning
confidence: 99%